The Influence of Parental Attachment and Autonomy on Juvenile Delinquency Among Vocational High School Students at Karsa Mulya in Palangkaraya - Rahmi Atika; M. Ali Sibram Malisi; Ummi Qudsiyah (Suluh: Jurnal Bimbingan dan Konseling, 2025)
This study reveals the phenomenon of juvenile delinquency among students of SMK Karsa Mulya by understanding the influence of parental attachment and independence on juvenile delinquency in SMK Karsa Mulya Palangkaraya students. This study focuses on the impact of parental attachment (father, mother) and independence on juvenile delinquency. The research design used is a multiple linear correlational research design with a sample of 114 from a population of 270 class X students. Sampling used probability sampling with a random sampling technique. Meanwhile, the calculation of data results using the SPSS 2018 application from 4 questionnaire instruments Inventory of Parent and Peer Attachment (IPPA), Autonomy Scale, and Self Report Delinquency Scale, with the results that there is no relationship between parental attachment and independence on juvenile delinquency, negatively correlated (-) namely the significance value of IPPA MOTHER p = 0.494> 0.05, not significant, IPPAFATHER: p = 0.889> 0.05 is not significant, while the autonomy value p = 0.172> 0.05 is not significant. However, there is a relationship if the three variables are combined, with a value of p = 0.006 <0.05, meaning that the higher the attachment of mother/father and independence, the lower the level of juvenile delinquency.